Culture works : space, value, and mobility across the neoliberal Americas - Dávila, Arlene M., 1965- (New York University Press, 2012)
Culture Works addresses and critiques an important dimension of the "work of culture", an argument made by enthusiasts of creative economies that culture contributes to the GDP, employment, social cohesion, and other forms of neoliberal development. While culture does make important contributions to national and urban economies, the incentives and benefits of participating in this economy are not distributed equally, due to restructuring that neoliberal policies have wrought from the 1980s on, as well as enduring inequalities of race, class and nationality. The cultural economy promises to make life better, particularly in cities, but not everyone can take advantage of it for decent jobs.